Clay mineralogy and chemical properties of soils in the north plateau of Santa Catarina state - Almeida, Jaime Antônio de; Ribeiro, Cesar Freitas; Oliveira, Marcus Vinícius Ribeiro de; Sequinatto, Leticia (Revista de Ciências Agroveterinárias, 2018)
In the North Plateau of Santa Catarina state, Brazil, there is little information about the mineralogical composition of the soils and a few soil profiles were described and characterized in the region. The two generalized soil maps of Santa Catarina indicate predominance of Inceptisols, Entisols and Oxisols, with hydromorphic soils occupying areas of floodplains. These soils occur in relief from plane to strong wavy, where small and medium rural farmers develop diversified crops, with significant areas with pine reforestation. This work aimed to increase the knowledge of the mineralogical and chemical properties of some of these soils developed from sedimentary rocks of different geological formations. Five soil profiles were described and sampled, included one oxisol and four Inceptisols. In fine earth, physical (sand, silt, clay) and chemical analyzes were performed (pH in water, organic carbon, Ca2+, Mg, K, Na, Al, H + Al) and based on these attributes was calculated effective CEC, CEC at pH7, sum of bases and base saturation. Mineralogical analyzes were conducted in the clay fraction of the B horizon of each soil, using X-ray diffraction techniques. All soils showed very acid reaction, with low sum of bases and base saturation and high levels of organic carbon and exchangeable Al. The clay mineralogy revealed predominance of kaolinite in all soils, with considerable amounts of gibbsite, and vermiculite with hydroxy-Al interlayered.